The effect of different agricultural waste on the population of phosphorus solubilizing bacteria and subsequent growth of aerobic rice / Azizul Azman - Azman, Azizul (Faculty of Plantation and Agrotechnology, 2016)
The location of Jasin area that nearby with plantation industrial area has inspired the use of organic waste from the industry produced as organic fertilizer. Organic fertilizer is source of nutrient to the microorganism especially Phosphorus Solubilizing Bacteria (PSB) which is can improve the available phosphorus in soil. This study conducted to determine the effect of different industrial organic waste to the population phosphorus solubilizing bacteria (PSB) subsequent on aerobic paddy. Observation was done in 6 week in green house UiTM Jasin. Main objective is to distinguish which organic waste is suitable in developing population of PSB. In this study, aerobic paddy was planted and organic waste which decanter cake, empty fruit bunch, paddy husk and rubber wood powder as treatment. There were five replication was made for each treatment. 3 gram ofPSB powder was applied on each pail. Plant height was recorded daily, starting from day 10 after transplant then continues until week 6 (day 45). Soil sample was collected every two week which is week 2, 4 and 6. For week 0, the sample was collected on day 10 after transplant. Sample was undergoing soil chemical analysis and microbial analysis in laboratory. Number of colonies varies on different organic waste counted manually. At the end of study shows plant with paddy husk treatment reach the most highest in height. Observation shows paddy plant produce yield at the same period but different in height. Data and result in this experiment has shown in the graph and chart.